Study Of the Influence of The Nature of Catalysts And Urea Concentrations on The Effect of Modification - Sativaldiev Aziz Kahramanovich (Euro Asian Journal Publishing, 2024)
Fabrics modified with the participation of ammophos as a catalyst gave high levels of crease resistance with the least loss of initial strength and a stable size, which indicates the high efficiency of this catalyst
Keywords: modification; concentration; urea; catalyst